Exploration of knowledge of cervical cancer and cervical cancer screening amongst HIV-positive women - Johanna E. Maree; Kefliwe A. Moitse (AOSIS, 2014)
Background: Although preventable, cervical cancer, an AIDS-related disease, is the second most common cancer amongst South African women and the most common cancer amongst black women. Objective: The objective of the study was to determine what women being treated for HIV and AIDS at a specific healthcare centre in Johannesburg knew about cervical cancer and cervical screening. Method: A survey design was used, with data gathered by means of a self-administered questionnaire. Convenience sampling selected 315 women to participate (n = 315). Descriptive statistics were used to analyse the data and chi-square testing found associations between categorical variables. Results: The majority of respondents (78.7%; n = 248) indicated that they had heard of cervical cancer and 62.9% (n = 198) knew about the Pap smear, with nurses and doctors being the primary source of information. Of the women who knew about the Pap smear, less than one-third had had a smear done, the main reason being fear of the procedure. Conclusion: The study provided evidence that women attending the specific HIV clinic were more knowledgeable about cervical cancer and screening than those of unknown HIV status involved in previous studies. Knowledge was still at a low level, especially when their exceptionally high risk was taken into account. Once again it was found that having knowledge did not necessarily mean having had a Pap smear, which remains a huge challenge in the prevention of cervical cancer.